A Porcine-Isolated Mycobacterium bovis Strain Exhibits Hypervirulence in a Murine Pulmonary Tuberculosis Model - Cuerda, Maria Ximena (2026)
Mycobacterium bovis is the causative agent of tuberculosis (TB) infecting a wide range of animal hosts, including humans. Domestic pigs (Sus scrofa domestica) are susceptible to different mycobacteria, particularly species within the Mycobacterium avium complex (MAC). However, in countries where bovine TB is endemic, such as Argentina, M. bovis is the most frequently reported species in pigs. This study aimed to evaluate the immune response and disease progression of a local strain (MB894) isolated from pigs and compare its pathogenicity with the highly virulent strain MB303, isolated from wild boar. Additionally, we sought to explore the genomic basis underlying the virulent phenotype of MB894. For this purpose, a murine infection model was used to assess pathogenicity, organ colonization, dissemination and cytokine induction. Whole-genome sequencing was performed to identify genetic features, including non-synonymous SNPs and INDELs, potentially associated with virulence. The severe immunopathogenesis produced by MB894, the higher multiplication rate in the evaluated organs, and the greater dissemination to other organs compared to MB303, combined with the cytokine levels induced by this strain, prompted us to classify MB894 as a hypervirulent strain. Genomic analysis revealed candidate genes that may be virulence factors contributing to this phenotype. In summary, MB894 represents a hypervirulent M. bovis strain with distinct pathogenic and genomic characteristics. These findings provide insights into the molecular determinants of virulence and highlight the need for further evaluation of identified gene candidates.